2020
DOI: 10.1055/a-1171-1322
|View full text |Cite
|
Sign up to set email alerts
|

Success of extracorporeal shock wave lithotripsy and ERCP in symptomatic pancreatic duct stones: a systematic review and meta-analysis

Abstract: Background and study aims Pain is the most frequent and dominant symptom of chronic pancreatitis. Currently, these patients are treated using a step-up approach, including analgesics and lifestyle adjustments, endoscopic, and eventually surgical treatment. Extracorporeal shock wave lithotripsy (ESWL) is indicated after failure of the first step in patients with symptomatic intraductal stones larger than 5 mm in the head or body of the pancreas. To assess the complete ductal clearance rate and pain relief after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 54 publications
(177 reference statements)
2
21
0
3
Order By: Relevance
“…Acute exacerbation is defined as acute pancreatitis during the follow‐up of chronic pancreatitis. The diagnosis of acute pancreatitis is based on “Japanese Guidelines for the Management of Acute Pancreatitis: Japanese Guidelines 2015.” 20 Complete stone removal was defined as no filling defects in the main PD on pancreatography with or without intraductal ultrasonography according to the previous reports 9,15,21–32 . Complete stone removal of pancreatic stones was additionally confirmed by computed tomography (CT) scan within 3 months after ERCP.…”
Section: Methodsmentioning
confidence: 99%
“…Acute exacerbation is defined as acute pancreatitis during the follow‐up of chronic pancreatitis. The diagnosis of acute pancreatitis is based on “Japanese Guidelines for the Management of Acute Pancreatitis: Japanese Guidelines 2015.” 20 Complete stone removal was defined as no filling defects in the main PD on pancreatography with or without intraductal ultrasonography according to the previous reports 9,15,21–32 . Complete stone removal of pancreatic stones was additionally confirmed by computed tomography (CT) scan within 3 months after ERCP.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that adding ESWL significantly decreases pain scores, yearly hospitalizations for pancreatitis, and opioid use[ 98 ]. A systematic review and meta-analyses of 22 ESWL ERCP studies noted high rates of complete stone fragmentation at 86.3% (95%CI: 76.0-94.0)[ 99 ]. The pooled percentage of patients with complete ductal clearance, however was 69.8% (95%CI: 63.8-75.5).…”
Section: Pancreatic Disease: Pancreatic Stones and Pancreatic Leaksmentioning
confidence: 99%
“…The pancreatic duct, also known as the Wirsung duct, connects the pancreas and intestine through the common bile duct. Its primary function is to transport enzymes and bicarbonate, which aid digestion and neutralize the duodenal pH, respectively [ 75 , 76 ]. Occlusion of the pancreatic duct may cause pancreatitis.…”
Section: Occlusions Of Exocrine Glands and Ductsmentioning
confidence: 99%
“…Occlusion of the pancreatic duct may cause pancreatitis. The occlusions of the ducts are directly proportional to the severity of the pancreatitis and depend on the duration of the disease [ 75 , 76 ].…”
Section: Occlusions Of Exocrine Glands and Ductsmentioning
confidence: 99%